Monitoring of single extracellular vesicle heterogeneity in cancer progression and therapy - Lee, Yoon-Jin; Chae, Shinwon; Choi, Dongsic (Frontiers in Oncology, 2023)
Cancer cells actively release lipid bilayer extracellular vesicles (EVs) that affect their microenvironment, favoring their progression and response to extracellular stress. These EVs contain dynamically regulating molecular cargos (proteins and nucleic acids) selected from their parental cells, representing the active biological functionality for cancer progression. These EVs are heterogeneous according to their size and molecular composition and are usually defined based on their biogenetic mechanisms, such as exosomes and ectosomes. Recent single EV detection technologies, such as nano-flow cytometry, have revealed the dynamically regulated molecular diversity within bulk EVs, indicating complex EV heterogeneity beyond classical biogenetic-based EV subtypes. EVs can be changed by internal oncogenic transformation or external stress such as chemotherapy. Among the altered combinations of EV subtypes, only a specific set of EVs represents functional molecular cargo, enabling cancer progression and immune modulation in the tumor microenvironment through their altered targeting efficiency and specificity. This review covers the heterogeneity of EVs discovered by emerging single EV analysis technologies, which reveal the complex distribution of EVs affected by oncogenic transformation and chemotherapy. Encouragingly, these unique molecular signatures in individual EVs indicate the status of their parental cancer cells. Thus, precise molecular profiling of circulating single EVs would open new areas for in-depth monitoring of the cancer microenvironment and shed new light on non-invasive diagnostic approaches using liquid biopsy.